Smart Hybrids: Humidity‐Driven Mechanical and Electrical Response of Graphene/Cloisite Hybrid Films (Adv. Funct. Mater. 14/2019). (1st April 2019) - Castaldo, Rachele; Lama, Giuseppe Cesare; Aprea, Paolo; Gentile, Gennaro; Ambrogi, Veronica; Lavorgna, Marino; Cerruti, Pierfrancesco
Abstract : In article number1807744, Gennaro Gentile, Veronica Ambrogi, and co‐workers present new graphene oxide (GO)/cloisite hybrid films as humidity‐driven mechanically and electrically responsive actuators and sensors. The hybrids show humidity‐triggered bidirectional bending whose extent is tuned by tailoring the GO/cloisite ratio. The thermally reduced GO/cloisite hybrids show moisture‐dependent electrical conductivity and generate contractile/relaxation stress upon humidity changes.